THE INFLUENCE OF USING PICTURES TOWARD STUDENTS’ ACHIEVEMENT IN PREPOSITION OF PLACE AT THE ELEVENTH GRADE STUDENTS OF SMK YADIKA LUBUKLINGGAU IN THE ACADEMIC YEAR OF 2013/2014 - Ardayati . (Universitas Batanghari Jambi, 2017)
Abstract: This research was a quasi experimental research by using non-equivalent control group design. The objective of this research was to find out whether there is a significant influence of using picture toward students’ achievement in preposition of place. This research used the eleventh grade students of SMK YADIKA Lubuklinggau as the research subject. There were two classes which were used in this research; they were class XIA which consisted of 42 students as the experiment class and class XIB which consisted of 42 students as the control class. The experiment class was taught by using picture whereas the control class was not taught by using picture. Both classes were chosen by using sensus sample as the sampling technique. The instrument used in this research was a written test about preposition of place consisting of multiple choice items. From the data analysis, it was found that the value of tcount = 6,72 while ttable or t (0,05) (82) = ±1,99. The result analysis showed that tcount was outside the acceptance area of H0 whether it was tested by using significance level ( ) = 0, 05 or ( ) = 0, 01. Therefore, the gain score in experiment and control class was found out very significant. Besides, the mean score of post-test in experiment class is 11,78 point was higher than the mean score of post-test in control class. The finding proved that students’ achievement in preposition of place of the class which was taught using picture was better than the class which was not taught using picture. Therefore, it can be concluded that picture has a significant influence toward students’ achievement in learning preposition of place. It was found that pictures can be used for teachers of English in teaching preposition of place. Keywords: Picture, Achievement, Preposition of Place